Topographical map of Ross County, Ohio / from actual surveys under the direction of H.F. Walling - Walling, Henry Francis; H.F. Walling's Map Establishment (New York : H. F. Walling's Map Establishment, 1860, 1860)
"Entered according to Act of Congress A.D. 1860 by H.F. Walling in the Clerk's Office of the U.S. Court for the Southern District of N.Y." Includes distance table, inset of South Salem, Lyndon, Massieville, Chillicothe, Yellow Bud Union, Lewisville, City of Chillicothe, E. Lanoham, Bainbridge-Paxton, Frankfort, Greenland--Deerfield, Lattaville, Deerfield, Roxabell-Concord, Londonderry Station (Liberty), Clarksburgh, Farmersville, Mooresville-Harrison, Bourneville Twin, Kingston, Hallsville-Colerain, Hopetown-Springfield, and Richmond-Jefferson. Color;